Strain hardening behaviour of polyethylene fibre reinforced ambient air cured geopolymer composite - Shaikh, Faiz; Fairchild, A. (2018)
This paper presents experimental investigation on strain hardening and deflection hardening behaviour of polyethylene (PE) fibre reinforced ambient air cured geopolymer composite. Comparison is also made with its counterpart ordinary Portland cement (OPC) based composite. The effect of different volume fractions of PE fibre on compressive strength, strain hardening and deflection hardening behaviour of above two composites is evaluated and a critical volume fraction of PE fibre for strain hardening and multiple cracking behaviour is identified. Results show that ambient air cured geopolymer composites exhibited better strain hardening, deflection hardening and multiple cracking behaviour than its counterpart OPC based composite containing same volume fraction of PE fibre. Compressive strength of OPC composite is higher than that of geopolymer composite. PF fibre volume fraction of 0.75–1.0% exhibited optimum fibre content for strain and deflection hardening behaviour of both composites.